Análisis de las técnicas de remoción de caries: láser y fresado convencional en la práctica odontológica. revisión bibliográfica - Gavin Ilvay, Danny Alexis (2025)
Introduction: Dental caries is a common condition in children and adults, traditionally treated with dental drills, an effective but uncomfortable procedure due to its friction, vibration and noise. Nowadays, dentistry is moving towards less invasive techniques, such as the use of lasers, which reduces trauma for the patient and significantly improves the clinical experience. Objective: The aim of this article was to evaluate the effectiveness of the laser caries removal technique in comparison with the traditional drilling technique through a literature review. Methodology: A documentary review of studies published between 2015 and 2024 in databases such as PubMed, Wiley and ScienceDirect was performed. The PICO strategy was applied to define the search with key terms. Randomized controlled trials comparing both techniques were included. Results: A total of 219 articles were obtained, of which 8 were selected for the investigation. In addition, it was found that, although conventional drilling is a faster process, the laser allows a more selective removal of the affected tissue, preserving a greater amount of healthy tooth structure. In addition, the laser provides a more comfortable experience, reducing the pain and fear associated with conventional drilling. Conclusions: It was determined that laser, compared to traditional drilling, offers similar efficiency in caries removal, but is more accepted by patients due to its less invasiveness. Although it requires more time, it reduces pain and discomfort, being ideal in patients who experience fear or anxiety.